Healthy eating promoting in a Brazilian sports-oriented school: a pilot study - Fábia Albernaz Massarani; Marta Citelli; Daniela Silva Canella; Josely Correa Koury (PeerJ, 2019)
Background Adolescents, particularly athletes, have high exposure to ultra-processed foods, which could be harmful to their health and physical performance. School environments are capable of improving eating patterns. Our study is aimed at capturing changes in students’ food consumption three years after they enrolled at an experimental school, considered a model of health promotion in Rio de Janeiro city. We also aimed to depict the promising nature of the healthy eating promotion program implemented in the school and share the learnings from its implementation. Methods Our pilot study was a follow-up on the implementation of a school garden, experimental kitchen activities, and health promotion classes. We evaluated 83 adolescent athletes’ food consumption twice during the study: at its beginning (2013) and end (2016), by administering a food frequency questionnaire (FFQ) that inquired about the frequency of foods consumed in the past week. To evaluate how effectively the activities were established, integrated, and sustained in schools, the Garden Resources, Education, and Environment Nexus (GREEN) tool was used, and the school’s adherence to the school garden program was classified as high (scored 47 points out of 57). Results In 2013, 89 adolescents (mean ± SD 11.9 ± 0.4 years, 54% male) participated in the study, of which 83 continued until 2016 (14.8 ± 0.5 years, 55% male). In 2013, the mean frequency of raw salad and fruits consumption was 1.4 (CI [1.0–1.9]) and 4.3 (CI [3.8–4.9]) days per week, respectively. Three years later, the frequency of raw salad and fruits consumption was 2.2 (CI [1.6–2.7]) and 5.0 (4.5–5.5), respectively. Considering that five meals were offered at school (five days/week), it may be possible to assume that the program raised awareness on the importance of healthy eating. Conclusion Our results suggest that such integrated healthy eating promotion programs may improve adolescent athletes’ eating habits, by increasing the frequency of their consumption of unprocessed foods. This pilot study’s results inspired us to implement an expanded project at the municipal level. Since 2018, teachers who participated in this program are working with Rio de Janeiro’s Municipal Secretary of Education for Coordination of Curricular Projects. Some learnings from this pilot study on implementing the garden/experimental kitchen project in this school are being applied in 65 schools of the municipal network: joint activities must be fostered among students, teachers, and parents; healthy eating needs to be a respected value among adolescent athletes and become an example for parents and teachers.